Effect Of Skim Latex On Mechanical Properties Of Tire Tread Compound - Mohamad Jafri, Nurul Husna (Universiti Sains Malaysia, 2022)
The vital effect of incorporation of skim latex in tire tread compound has been investigated by preparing seven variations of blending ratios of skim rubber/SMR 10 varies form 100:0 to 0:100. The mechanical properties of the rubber vulcanizates have been examined thenceforth. This method has been studied in recent years that the inclusive compound incorporated with skim latex ought to have an effect on curing characteristics of the vulcanizates. Predominantly, the administration of this particular investigation is to validate the admissibility of skim latex to be integrated in tire tread compound as well as substituting natural rubber in the development of rubber compound. A researcher had executed an experimentation correlated to skim latex/NR combination wherein high protein content and fatty acid in skim rubber is distinctly affect the vulcanization conduct of rubber compound. Generally, few testing had been performed to investigate the mechanical properties of skim rubber/SMR 10 blend namely abrasion test, tensile, swelling index test, and tear test. The experimental method and sample instruction were referred to ASTM D228, ASTM D412-98, ASTM 624 and ASTM D3616. The presence of protein is perceived as the strengthening effect, bonding the molecular chain of rubber. However, it was found that the mechanical properties of SMR 10/skim rubber blend prospect to decrement, wherein the abrasion resistance, tear strength and tensile strength has diminished in correspondence to the increasing portion of skim rubber. In spite of that, the cure characteristic of rubber composites significantly increased coherently with the proportional increment of skim rubber from 20 to 100 pphr.